The Influence of Accountability, Transparency, and Internal Control on the Budget Implementation Performance of the Binjai City Regional Government - Indah Dwi Arnasyah; Khairina Tambunan; Yenni Samri Juliati Nasution (Pusat P2M Politeknik Negeri Batam, 2025)
This study aims to examine the impact of accountability, transparency, and internal control on budget management performance. The population consists of four SKPDs (Regional Work Units) in Binjai City, with a sample of 90 respondents. Primary data were collected through questionnaires distributed to respondents, who included department heads, finance heads, and finance staff, with time provided for responses. The sampling method employed was purposive sampling, resulting in 90 respondents. The analysis utilized multiple linear regression with SPSS (Statistical Product and Service Solutions) version 25.0. The findings indicate that accountability, transparency, and internal control each have a positive effect on budget management performance in local government. These results support all the hypotheses formulated in the study.